Tentang Kedudukan Hak Angket dalam Sistem Ketatanegaraan Republik Indonesia - Alfania Zefanya Tumewu; Yoan B. Runtunuwu; Reynold Simandjuntak (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Within the structure of the Indonesian constitution, the House of Representatives (DPR) holds the Right of Inquiry as one of its key oversight mechanisms. This authority enables the DPR to examine government policies deemed detrimental to the public or inconsistent with prevailing regulations. In practice, the Right of Inquiry serves as a tool to uphold transparency, accountability, and the balance of power between the legislative and executive branches. However, its effectiveness is often hindered by various challenges, including politicization, political dominance within the parliament, and the limited implementation of investigation outcomes. To enhance its function, it is essential to reinforce legal frameworks, improve the integrity of DPR members, and foster synergy among governmental institutions. With proper management, the Right of Inquiry can significantly contribute to strengthening the democratic system and promoting a government that is more responsive to public needs.